The Urgency of Character Education in Facing the Moral Crisis of the Young Generation - Egi Divya Tyara Bilkis; Yusuf Tri Herlambang; Aisha Nadia (CV. Ksatria Siliwangi, 2025)
Character education plays a crucial role in addressing the moral crisis affecting the younger generation. Rapid developments in society have brought about various changes. Technological advancements, globalization, and rapid social change have both positive and negative impacts on the attitudes and behavior of the younger generation. Various problems have emerged, including a decline in manners, deviant behavior, a lack of responsibility, and a weakening of moral values, which pose serious challenges that require collective attention. This article aims to discuss the urgency of character education in addressing the moral crisis among the younger generation and the role of education in shaping a moral and ethical personality. The method used in this article is a qualitative method with a literature study approach, examining various books, scientific journals, and articles relevant to the topic of education. The results of the study indicate that character education, implemented in an integrated manner in the learning process, is able to instill moral values, ethics, responsibility, and discipline in students. Character education is not only the responsibility of educational institutions but also requires cooperation between families and the community. The conclusion of this article confirms that strengthening character education is a strategic and urgent step in developing a young generation with morals and strong character, capable of facing the challenges of modern development. The research also shows that modern developments, family, peers, the school environment, and the social environment have a significant impact on students' moral decline.